Are Checking Accounts in American Banks Permissible Under Islamic Laws? - Ail F. Darrat (International Institute of Islamic Thought, 1985)
The purpose of this note is to stimulate the thought of Muslim scholars about a neglected aspect of American banking business. namely the payment of interest on demand deposits (checking accounts). Demand deposits represent funds that commercial banks use to extend loans to the public and purchase interest-bearing securities. The revenues from these activities are a major source of income for commercial banks. Consequently, fierce competition exists among banks to attract such funds: However, competition for these fonds. until recently, could not take the form of an explicit interest rate because the American banking laws prohibit the payments of explicit interest rates on demand deposits .. Existing laws have relaxed this prohibition for some forms of demand deposits (e.g. Negotiable Orders of Witndrawals NOW accounts), though the prohibition still holds in the case of what is commonly called in the banking jargon regular checking accounts, i.e .. checking accounts that do not explicitly yield interest to the holders. Because of the intensity of competition among commercial banks to attract public deposits. and  in the presense of the legal prohibition against explicit interest payments on regular checking accounts banks have devised alternative outlets to compete for the checking accounts funds. Perhaps the most obvious alternative is for a bank to reduce (or remit) charges to depositors for the use of bank payments services below the cost to the bank of providing those services. Others take the form of for example, providing a wide range of cash management services at very nominal fees and occasional gifts. In economic literature these are called implicit interest rates, and many recent empirical studies have established the fact that commercial hanks in the U.S. do in fact pay high implicit interest rates on non-interest bearing demand deposits of approximately equal value to the rate which would be explicitly paid in the abscence of the legal prohibition ...